Hellinsia mongolica - Ustjuzhanina, Anna (Zenodo, 2017)
Hellinsia mongolicа (Zagulajev et Pentshukovskaja, 1972) Material examined . 1 ♂ (CUK), Azas, 11.vi.1988, V. Zinchenko; 1 ♀ (CUK), Kyzyl, 14.–15.vi.2001, P. Ustjuzhanin; 1 ♂ (CUK), Khanmalyg, 3.–4.vii.2004, O. Kosterin. Distribution. The mountains of South Siberia, Mongolia, Yakutia, China. Published as part of Ustjuzhanina, Anna, 2017, Pterophoridae (Lepidoptera) fauna of the Republic of Tuva, pp. 317-328 in Zootaxa 4319 (2) on page 326, DOI:10.11646/zootaxa.4319.2.3, http://zenodo.org/record/889135